2017
DOI: 10.1111/cbdd.13112
|View full text |Cite
|
Sign up to set email alerts
|

Potential biological targets for bioassay development in drug discovery of Sturge–Weber syndrome

Abstract: Sturge-Weber Syndrome (SWS) is a neurocutaneous disease with clinical manifestations including ocular (glaucoma), cutaneous (port-wine birthmark), neurologic (seizures), and vascular problems. Molecular mechanisms of SWS pathogenesis are initiated by the somatic mutation in GNAQ. Therefore, no definite treatments exist for SWS and treatment options only mitigate the intensity of its clinical manifestations. Biological assay design for drug discovery against this syndrome demands comprehensive knowledge on mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 114 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…There are other treatment approaches, such as modulation through bioactive compounds, that induce fibronectin expression or carbonic anhydrase enzyme and acetylcholinesterase, which focus on decreasing the severity of glaucoma. This approach includes sirolimus, which inhibits the mTOR pathway that is characteristically hyperactivated in SWS and other vascular alterations [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are other treatment approaches, such as modulation through bioactive compounds, that induce fibronectin expression or carbonic anhydrase enzyme and acetylcholinesterase, which focus on decreasing the severity of glaucoma. This approach includes sirolimus, which inhibits the mTOR pathway that is characteristically hyperactivated in SWS and other vascular alterations [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although clinical data may be useful in this process, such data are not entirely decisive, given that at a clinical level there may be silent courses, as in the cases of CCT [ 58 ] and small CAs [ 31 ] or clinical manifestations that are closely similar, such headaches and seizures that are present in most of the different vascular malformation cases [ 17 , 20 , 32 , 33 , 49 , 50 , 51 , 60 , 62 , 68 ]. An example of a fairly useful clinical feature is port wine stain in the case of SWS [ 63 , 64 , 65 ]; however, this syndrome will only occur in 8% to 33% of the subjects with the skin mark [ 70 ]. In addition, SWS may be present without the presence of port wine stain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The α subunit of G protein (a GNAQ expression product) is then released and activates enzymes and effector proteins involved in signaling pathways necessary for vascular development. Alterations of GNAQ are indicated in SWS pathogenesis [159,164,165] exclusively in tissue with capillary malformation [167,168]. On the other hand, Sundaram et al suggested that the variation p.Arg183Gln, which is the most common alteration in SWS, is not only linked with vascular malformations, but may also affect brain parenchyma, which could explain the brain pathology present in SWS [169,170].…”
Section: Arch Med Sci 11mentioning
confidence: 99%